7 - 9w = - 29
Subtract 7 from both sides
- 9w = - 36
Divide by - 9 on both sides
w = 4
Answer:
I thing Kaleigh read 1.5 more than Austin
Step-by-step explanation:
Answer:
30t - 4
Step-by-step explanation:
Remember to follow PEMDAS. First, distribute -6 to all terms within the parenthesis:
2 -6(-5t + 1) = 2 + (-6 * -5t) + (-6 * 1)
2 + (30t) + (-6) = 2 + 30t - 6
Simplify. Combine like terms:
2 + 30t - 6 = 30t + (-6 + 2) = 30t - 4
30t - 4 is your answer.
~
Answer:
![\large\boxed{\sqrt[3]{3^{15}}=243}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B%5Csqrt%5B3%5D%7B3%5E%7B15%7D%7D%3D243%7D)
Step-by-step explanation:
![\sqrt[3]{3^{15}}\\\\\text{use}\ (a^n)^m=a^{nm}\\\\=\sqrt[3]{3^{5\cdot3}}=\sqrt[3]{(3^5)^3}\\\\\text{use}\ \sqrt[n]{a^n}=a\\\\=3^5=243](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B3%5E%7B15%7D%7D%5C%5C%5C%5C%5Ctext%7Buse%7D%5C%20%28a%5En%29%5Em%3Da%5E%7Bnm%7D%5C%5C%5C%5C%3D%5Csqrt%5B3%5D%7B3%5E%7B5%5Ccdot3%7D%7D%3D%5Csqrt%5B3%5D%7B%283%5E5%29%5E3%7D%5C%5C%5C%5C%5Ctext%7Buse%7D%5C%20%5Csqrt%5Bn%5D%7Ba%5En%7D%3Da%5C%5C%5C%5C%3D3%5E5%3D243)